2012
DOI: 10.1016/j.jad.2012.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Sensation seeking as risk factor for suicidal ideation and suicide attempts in adolescence

Abstract: Background High sensation seeking in adolescence is associated with engagement in risk-taking behaviors, especially substance use. Although depressed adolescents are prone to increased risk-taking, and suicidal behavior can be considered within the spectrum of risk-taking behaviors, the relationships between sensation seeking, depression, and suicidal behavior have not been explored. Methods A self-report questionnaire assessing sensation seeking, depression, substance use problems, and suicidal ideation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 105 publications
4
41
0
3
Order By: Relevance
“…Sensation seeking is correlated with a variety of externalizing behaviors and disorders, including alcohol and drug use and sexual risk-taking, as well as suicidality and self-injury (Charnigo et al, 2013; Knorr, Jenkins, & Conner, 2013; Ortin, Lake, Kleinman, & Gould, 2012; Quinn & Harden, 2013). Thus the current results suggest that sensation seeking is a promising candidate for a “missing link” that connects CSA with an array of clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Sensation seeking is correlated with a variety of externalizing behaviors and disorders, including alcohol and drug use and sexual risk-taking, as well as suicidality and self-injury (Charnigo et al, 2013; Knorr, Jenkins, & Conner, 2013; Ortin, Lake, Kleinman, & Gould, 2012; Quinn & Harden, 2013). Thus the current results suggest that sensation seeking is a promising candidate for a “missing link” that connects CSA with an array of clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that, while there are inconsistencies and confusing findings given the interrelationship between aggression and impulsivity, the relationship between aggression, impulsivity, and suicidality is well-established. Ortin et al (2012) examined the relationship between sensation seeking in adolescence and suicidality. Sensation seeking was related to both suicidal ideation and suicide attempt, even after controlling for depression and substance use.…”
Section: Impulsivity and Suicide Riskmentioning
confidence: 99%
“…Adolescence and emerging adulthood are characterized by increases in a number of suicide risk factors such as substance abuse (e.g., Harford, Grant, Yi, & Chen, 2005), depression (e.g., Reinherz, Paradis, Giaconia, Stashwick, & Fitzmaurice, 2003), and sensation seeking and risky behaviors (Ortin, Lake, Kleinman, & Gould, 2012). Additionally, these developmental periods are characterized by significant life transitions, such as graduating high school and entering college or the workforce.…”
Section: Introductionmentioning
confidence: 99%